Vitamin D status in Faroese adults and its association with inflammatory bowel diseases - a cross-sectional study from the FarGen 2 project - Randi Næss Lisberg; Kári Rubek Nielsen; Leivur Nattestad Lydersen; Katrin Didriksen Apol; Jóngerð Midjord; Olivia Gray; Melissa Hendershott; Marin Strøm; Noomi Oddmarsdóttir Gregersen (International Journal of Circumpolar Health)
Vitamin D is vital for physiological functions and is obtained primarily through sunlight and a few dietary sources. With limited sunlight exposure, the Faroe Islands face challenges in maintaining sufficient levels of vitamin D, while the Faroese population has documented the highest incidence and prevalence of inflammatory bowel disease worldwide. This study investigates vitamin D status among Faroese adults and its association with inflammatory bowel disease as well as other self-reported diseases in a subset of the Faroe Genome Project 2. Cross-sectional study including 1,748 participants aged 18–86 years. Among participants, 74.3% maintained sufficient vitamin D levels, while 25.7% were insufficient (<50 nmol/l). Individuals with conditions like hypertension, type 2 diabetes, and inflammatory bowel disease showed significantly higher rates of vitamin D sufficiency compared to those without these conditions. Notably, 83% of participants with inflammatory bowel disease had sufficient vitamin D. Our data reveal higher vitamin D levels compared to previous studies in the Faroe Islands. Furthermore, contrary to our hypothesis, our data shows higher vitamin D levels for participants reporting diseases including inflammatory bowel disease, indicating patients with inflammatory bowel disease can attain high vitamin D levels, which is of considerable clinical importance.